The development of syllable structure in cape verdean creole - Andrei A. Avram (Bucharest Working Papers in Linguistics, 2008)
The paper examines syllable restructuring in the Santiago variety of Cape Verdean Creole. It is shownthat currently attested forms reflect to some extent the syllable structure in earlier stages of the language. Severalstrategies for syllable restructuring are identified and illustrated. These repair strategies are shown to operate inMandinka and Wolof, the two main substrate languages of Cape Verdean Creole, as well as in Guinea-BissauCreole, a closely related Portuguese-lexified creole. A tentative relative chronology of the stages conducive tothe present syllable structure of Cape Verdean Creole is outlined. Also discussed are some of the theoreticalimplications of the findings.